2018
DOI: 10.3390/en11113172
|View full text |Cite
|
Sign up to set email alerts
|

An Approach for Estimating Solar Photovoltaic Potential Based on Rooftop Retrieval from Remote Sensing Images

Abstract: Solar energy is the most clean renewable energy source and has good prospects for future sustainable development. Installation of solar photovoltaic (PV) systems on building rooftops has been the most widely applied method for using solar energy resources. In this study, we developed an approach to simulate the monthly and annual solar radiation on rooftops at an hourly time step to estimate the solar PV potential, based on rooftop feature retrieval from remote sensing images. The rooftop features included 2D … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 38 publications
0
33
0
2
Order By: Relevance
“…Several studies have assessed the available rooftops footprint to estimate the solar potential in different locations based on different approaches. For example, Song et al [20] have assessed rooftop availability s in Chao Yang District of Beijing, China and found that 678 805 m 2 of usable rooftop area could host 63.78 GWh per year of PV electricity generation. The technical potential for rooftop solar PV has also been estimated across the USA [21,22], where it was found that 8.13 billion m 2 of rooftops are suitable to host 1118 GW of PV capacity.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have assessed the available rooftops footprint to estimate the solar potential in different locations based on different approaches. For example, Song et al [20] have assessed rooftop availability s in Chao Yang District of Beijing, China and found that 678 805 m 2 of usable rooftop area could host 63.78 GWh per year of PV electricity generation. The technical potential for rooftop solar PV has also been estimated across the USA [21,22], where it was found that 8.13 billion m 2 of rooftops are suitable to host 1118 GW of PV capacity.…”
Section: Introductionmentioning
confidence: 99%
“…La energía solar es el recurso energético más abundante en la naturaleza, alrededor de 885 millones de TWh alcanzan la superficie terrestre cada año. El uso de la energía solar se constituye, por tanto, en un buen prospecto para el desarrollo sostenible [1], [2].…”
Section: Introductionunclassified
“…The widest field for RES building integration is found in the urban environment. Considerable research has been carried out to determine the PV [24][25][26][27][28][29][30][31][32] and wind potential [33][34][35][36] in urban areas and buildings.…”
Section: Introductionmentioning
confidence: 99%